Study guides

☆☆

Q: What is positive ten minus negative ten?

Write your answer...

Submit

Still have questions?

Related questions

Six minus negative four is positive ten, because subtracting a negative is the same as adding a positive.

-10-(-60)=50 A negative and a negative equals a positive. Therefore, negative ten minus negative sixty is the same as negative ten PLUS sixty. Sixty minus ten equals fifty.

The quotient of a positive integer by a negative is always negative. Say this to yourself a couple times: "MULTIPLICATION: minus times minus is plus (negative x negative = positive).....minus times plus is minus (negative x positive = negative).....plus times plus is plus (positive x positive = positive) DIVISION: minus divi minus is plus (negative ÷ negative = positive)......minus divi plus is minus (negative ÷ positive = negative).....plus divi plus is plus (positive ÷ positive = positive)"

A positive minus a negative is a positive.

Positive (Plus) times Negative (Minus) always equals a negative (minus).

Because "minus a negative" is tha same as "plus a positive". So, a positive minus a negative is a positive plus a positive which is a positive.

9 - (-1) = +10 positive nine minus negative one equals positive ten

I honestly don't know :D but heres something to help you "MULTIPLICATION: minus times minus is plus (negative x negative = positive).....minus times plus is minus (negative x positive = negative).....plus times plus is plus (positive x positive = positive) DIVISION: minus divi minus is plus (negative ÷ negative = positive)......minus divi plus is minus (negative ÷ positive = negative).....plus divi plus is plus (positive ÷ positive = positive)"

Positive 3 plus negative 5 minus negative 2 minus positive 4 is equal to -4.

(-10) - (+7) = -10 - 7 = -17

A negative minus a positive is a negative. i.e -1-(+1)= -2

It depends. (a) a positive minus a smaller positive is positive, (b) a positive minus a positive of the same size is zero, and (c) a positive minus a bigger positive is negative. For example, (a) 8 - 6 = 2 (b) 8 - 8 = 0 (c) 8 - 11 = -3

People also asked